2019
DOI: 10.1177/1049909118824031
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Polypharmacy in Elderly Patients With Cancer Pain

Abstract: Objective: Polypharmacy (PP) is a burden in elderly patients with cancer pain; however, risk factors for PP remain unclear. The purpose of this study was to investigate the risk factors for PP in this patient population. Methods: We retrospectively reviewed the medical charts of patients aged 65 years with cancer pain who were treated at Osaka University Hospital between February 2014 and June 2016 according to the World Health Organization 3-step ladder for cancer pain relief. We defined PP as 5 medications a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…We observed that participants with poorer functional status also had higher odds of polypharmacy, and the association was still statistically significant after additionally adjusting for lifestyle factors and comorbidities (OR, 1.72; 95% CI, 1.31–2.26 for poor functional status vs excellent functional status). This finding is in agreement with previous studies, which investigated the associations between patient characteristics and polypharmacy in older patients with cancer and observed that poorer ECOG performance status was significantly associated with polypharmacy [ 35 , 36 ]. Interestingly, in our cohort, age was not associated with polypharmacy any more in the full model, in which we included more clinically relevant variables than age, like the functional status and 13 diseases/conditions.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that participants with poorer functional status also had higher odds of polypharmacy, and the association was still statistically significant after additionally adjusting for lifestyle factors and comorbidities (OR, 1.72; 95% CI, 1.31–2.26 for poor functional status vs excellent functional status). This finding is in agreement with previous studies, which investigated the associations between patient characteristics and polypharmacy in older patients with cancer and observed that poorer ECOG performance status was significantly associated with polypharmacy [ 35 , 36 ]. Interestingly, in our cohort, age was not associated with polypharmacy any more in the full model, in which we included more clinically relevant variables than age, like the functional status and 13 diseases/conditions.…”
Section: Discussionsupporting
confidence: 93%
“… 43 , 44 For instance, multimorbidity could complicate or delay cancer, anxiety, depression, and other diagnoses, limit the possibility to receive optimal treatments, delay their initiation, decrease adherence and persistence, increase the risk of polypharmacy and adverse drug interactions. 16 , 43 - 48 Most importantly, a high burden of comorbid conditions leads to decreased survival in cancer. 23 , 30 , 44 , 48 - 50 …”
Section: Discussionmentioning
confidence: 99%
“…43,44 For instance, multimorbidity could complicate or delay cancer, anxiety, depression, and other diagnoses, limit the possibility to receive optimal treatments, delay their initiation, decrease adherence and persistence, increase the risk of polypharmacy and adverse drug interactions. 16,[43][44][45][46][47][48] Most importantly, a high burden of comorbid conditions leads to decreased survival in cancer. 23,30,44,[48][49][50] As a retrospective observational study, although we were unable to determine the causal relationships between multimorbidity and anxiety and depression, our findings regarding these associations are valuable.…”
Section: Discussionmentioning
confidence: 99%
“…MMB impacts people with cancer directly through an increased physiological burden of disease and/or indirectly through healthcare factors related to treatment decision-making and the increased complexity of care (15). For example, MMB can complicate and delay cancer and other diagnoses, increasing treatment complexity, risk of polypharmacy, and/or other redundancies in care (16)(17)(18)(19)(20). Critically, cancer patients with MMB are less likely to be offered active or curative therapies (21)(22)(23), despite growing evidence that such treatments are tolerated and effective for some patients with cancer MMB (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%